1825 N.H. Laws 74, § 2 - (:unkn) unknown (My University, 1825)
An Act to Regulate the Keeping and Selling, and Transporting of Gunpowder, § 2: Requiring storage of less than 75 pounds of gunpowder in tin cannister or other noncombustible vessel(s).
Keywords: GUNPOWDER - STORAGE